A previous champagne tap reduces the probability of traumatic lumbar puncture in the following procedure - Sievänen Harri; Kari Juho; Huurre Anu; Palmu Sauli (Nature Research, 2025)
A cerebrospinal fluid (CSF) sample containing no red blood cells (RBC), colloquially known as a champagne tap, is an ideal outcome of a lumbar puncture (LP). In this pseudoprospective study of 2573 patients aged from 0 days to 95 years, we examined in four different age categories (neonates and infants, children and adolescents, adults, and older adults) whether a champagne tap in the patient’s first LP procedure and a shorter time than 1 week between the two successive procedures are independently associated with fewer blood-contaminated CSF samples (traumatic LP) in the following procedure. One out of five CSF samples from the patient’s first LP procedures were RBC-free on average, varying from about 9% in neonates and infants to about 36% in children and adolescents. The mean incidence of champagne taps was 19.5%. According to binary logistic regression, a champagne tap in the previous LP procedure significantly determined whether the following procedure was not blood-contaminated. The odds of traumatic LP were halved or even reduced tenfold after a champagne tap. Less than a week between the two successive procedures, in turn, multiplied the odds of traumatic LP in the latter even more than tenfold. A champagne tap was not significantly associated with traumatic LP in the following procedure among pediatric patients. If the patient’s condition or therapy plan permits and the blood contamination can compromise the reliability of the CSF-based analysis and consequent diagnosis, postponing the LP procedure by several days is advisable to improve the odds of receiving a high-quality CSF sample.